2011
DOI: 10.1111/j.1525-1594.2011.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research With Synthetic Copolymer‐Coated Cardiopulmonary Bypass Circuits: Inflammatory and Thrombogenicity Analysis

Abstract: This study aimed to assess complement system activation and index of thrombogenicity and platelet aggregation between synthetic copolymer-coated cardiopulmonary bypass (CPB) circuit and conventional CPB circuit. Twenty-six pigs were equally divided into two groups--the conventional group and the coated group. They were placed on CPB for 90 min, and blood samples were collected at three different time points (T0, right before CPB establishment; T1, 45 min after starting CPB; and T2, 90 min after starting CPB) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Other variables were assessed by least amount of studies, but also showed relevant results to clinical practice. Gabriel et al [ 32 ] sought to investigate the use of a coated synthetic copolymer (methacrylate), showing lower circuit platelet aggregation, but no differences in the number of leukocytes, compared with the control group. The use of mini-sternotomy was studied by Hayashi et al [ 33 ] showing no difference with the traditional technique at the end of procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Other variables were assessed by least amount of studies, but also showed relevant results to clinical practice. Gabriel et al [ 32 ] sought to investigate the use of a coated synthetic copolymer (methacrylate), showing lower circuit platelet aggregation, but no differences in the number of leukocytes, compared with the control group. The use of mini-sternotomy was studied by Hayashi et al [ 33 ] showing no difference with the traditional technique at the end of procedure.…”
Section: Resultsmentioning
confidence: 99%
“…This activation can improperly stimulate biological processes that may contribute to the development of postoperative complications resulting from the dysfunction of blood cells, coagulation, fibrinolysis, and the kinin-kallikrein and immune systems (1416). Various modifications to the inner surface of the CPB circuit, including heparin- and polymer-coating, reduce adverse effects on complement activation, blood coagulation, proinflammatory cytokines and improve clinical outcomes (17–20). The C5 complement inhibitor pexelizumab and a complement factor 1 esterase inhibitor have been tested clinically (21) and in an animal study (22) for their abilities to reduce complement activation during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Edmo Atique Gabriel et al. of the Albert Einstein Jewish Hospital, São Paulo, Brazil assessed the complement system activation and index of thrombogenicity and platelet aggregation between a synthetic copolymer‐coated cardiopulmonary bypass (CPB) circuit and the conventional CPB circuit. Twenty‐six pigs were equally divided into two groups—the conventional group and the coated group.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%